E-Business: A global scenario - Borsella, Ralph (New Jersey Lanrye International, 2015)
This book consists of studies that employ empirical and theoretical/conceptual approaches to bring to the foreground global acceptance of electronic business (e-business) and other important applications and conceptualization in this field. As our expertise of the e-business phenomenon continues to develop and progress, it is relevant that new knowledge and information be made available. This book tries to give value to e-business researchers and practitioners, with knowledge derived from various regions of the world. This edited book encompasses a vast range of interesting, topical, and timely issues on the acceptance of e-business concepts to nonprofit organizations, and the formulation of a service innovation model that are referred from various sources of information. This book can be used as a reference for information seekers who want to comprehend arising conceptualization, processes, and behaviors in the e-business domain.
Keywords: Business -- Data processing; Computational intelligence; IT in Business